Implementasi Manajemen Strategik Dalam Meningkatkan Mutu Pendidikan (Studi Pada Pada SMAS Widya Nusantara, Bekasi) - Dian Suarditini; Putri Dhea Jasmine; Tegar Setiawan; Reza Almasyah Pratama (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
Strategic management is a process within the organization to assist and formulate what must be achieved in order to produce something of value. The position of strategic management in an organization is very important. Because the existence of strategic management produces a framework in overcoming every strategic problem within the organization, strategic management also makes an organization think strategically and think more innovatively. Solving a problem by Realizing and Thinking more distinctions built from a more thorough analysis, max will create a useful and fruitful result. As is the case with quality education, it will be carried out properly and usefully if the school implements the strategic management that has been formulated previously in accordance with the existing vision and mission. However, judging from the existing problems, such as the lack of school management at Widya Nusantara Bekasi Private High School. Therefore the authors are interested in conducting analysis or research with the aim of analyzing and analyzing profiles, implementation and evaluation of strategic management in an effort to improve the quality of education. This research is a qualitative descriptive study conducted at Widya Nusantara Private High School, Bekasi. This study conducted research subjects to school principals, vice principals, treasurers, administrative staff, school committees and teachers. In the technique of data collection is done through observation, and interviews. The results of this study indicate that the profile of Widya Nusantara Private High School, Bekasi drives a vision, mission, goals, objectives and profile of school resources. Strategy implementation at Widya Nusantara Private High School, Bekasi is carried out through internal and external school environmental activities which are described through the school's organizational structure, teamwork and division of school assignments, study days and times, financing assets, curriculum, school promotion, new student admissions, school culture , code of ethics, school virtues, geographical environment, demographics, cultural environment and community appreciation, government regulations, developments in science and technology, involvement of school committees, partner institutions, alumni and implementation strategies in an effort to meet national education standards. The evaluation at Widya Nusantara Private High School, Bekasi is carried out continuously by involving top management and all school personnel both in the short term and long term through school selfevaluation instruments, teachers and benchmarking to improve school performance and education quality.